Evaluation of Therapeutic Potential of Chenopodium Album L. Extract Against Cyclophosphamide Induced Reproductive Damages in Male Rats - Kumar Verma, Manish; Hasan Ahmad, Abul; Prasad, Niharika (The Indian Journal of Animal Reproduction, 2025)
Chenopodium album, a leafy plant belonging to the family Amaranthaceae, is highly nutritious and holds significant  medicinal value. Traditionally, it is recognized for its antioxidant, anti-parasitic, immunostimulant, antimicrobial, and  anti-inflammatory properties. This study investigates the therapeutic potential of hydroethanolic extract of C. album (CAHE) against cyclophosphamide (CYP)-induced reproductive toxicity in male albino rats. CYP, a cytotoxic chemo therapeutic agent, is known to induce oxidative stress, impair sperm quality, and disrupt hormonal balance. The study  employed various reproductive and oxidative stress parameters to assess the protective effects of CAHE. Results revealed  that CAHE significantly (p
Keywords: Antioxidants; Chenopodium album; cyclophosphamide; reproductive health